The Grade‐Level and Cumulative Outcomes of Absenteeism. Issue 4 (19th March 2021) - Ansari, Arya; Gottfried, Michael A.
Abstract : Nationally representative data from the Early Childhood Longitudinal Study Kindergarten Class of 2011 ( n  = 14, 370) were used to examine the grade‐level and cumulative outcomes of school absenteeism between kindergarten and fifth grade for students' school performance in the United States. Students who were more frequently absent in any year of elementary school demonstrated lower academic, executive function, and socioemotional outcomes. Although there was little variation in the magnitude of associations across grade levels, there was evidence of cumulative associations. Specifically, students who were consistently absent throughout elementary school tended to have lower outcomes across developmental domains in the long‐term. The negative links between absenteeism and outcomes were larger for Black than White students, but few other subgroup differences emerged.